2015
DOI: 10.1063/1.4906605
|View full text |Cite
|
Sign up to set email alerts
|

The photodissociation dynamics of alkyl radicals

Abstract: The photodisscociation dynamics of the alkyl radicals i-propyl (CH(CH3)2) and t-butyl (C(CH3)3) are investigated by H-atom photofragment imaging. While i-propyl is excited at 250 nm, the photodynamics of t-butyl are explored over a large energy range using excitation wavelengths between 347 nm and 233 nm. The results are compared to those obtained previously for ethyl, CH3CH2, and to those reported for t-butyl using 248 nm excitation. The translational energy (ET) distribution of the H-atom photofragments is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 53 publications
(73 reference statements)
2
21
0
Order By: Relevance
“…200 Time resolved photoelectron spectroscopy data obtained following excitation at  = 330 and 266 nm were interpreted as implying an important role for excited state C-C bond extension, 201 but PTS measurements were required to confirm the importance of both C-C and C-H bond fission pathways (yielding CH3 + CH3CCH3 and H + (CH3)2CCH2 products, respectively) following excitation at  = 248 nm. Neither product TKER distribution nor the deduced product branching fraction approximate that expected on the basis of 'statistical' dissociation on the ground state PES 202 and later ion imaging studies 194 confirmed that the H atom photofragments from photolysis at wavelengths within all three of these UV absorption bands display bimodal velocity distributions reminiscent of those from photolysis of the smaller alkyl radicals. All of these data imply a substantial role for excited state C-H bond fission processes following UV photoexcitation of alkyl radicals.…”
Section: Alkyl Radicalsmentioning
confidence: 78%
See 1 more Smart Citation
“…200 Time resolved photoelectron spectroscopy data obtained following excitation at  = 330 and 266 nm were interpreted as implying an important role for excited state C-C bond extension, 201 but PTS measurements were required to confirm the importance of both C-C and C-H bond fission pathways (yielding CH3 + CH3CCH3 and H + (CH3)2CCH2 products, respectively) following excitation at  = 248 nm. Neither product TKER distribution nor the deduced product branching fraction approximate that expected on the basis of 'statistical' dissociation on the ground state PES 202 and later ion imaging studies 194 confirmed that the H atom photofragments from photolysis at wavelengths within all three of these UV absorption bands display bimodal velocity distributions reminiscent of those from photolysis of the smaller alkyl radicals. All of these data imply a substantial role for excited state C-H bond fission processes following UV photoexcitation of alkyl radicals.…”
Section: Alkyl Radicalsmentioning
confidence: 78%
“…These C2H3 products are then proposed to release an H atom, which could offer a possible rationale for the reported slow build-up rate of the atomic products, 193 though it is difficult to reconcile the observed H atom velocity distribution with such a mechanism. 194 Finally, we note that C-C bond fission is also thermodynamically allowed when exciting in this wavelength range, but we are not aware of any reports of such product formation.…”
Section: Alkyl Radicalsmentioning
confidence: 90%
“…Although such a * excited valence state is inaccessible from the ground state equilibrium, it will decrease in energy upon stretching a C-C bond, because it corresponds to the dissociative coordinate to dimethylcarbene + CH3. This hypothesis has been further developed in an attempt to rationalize the results of several H-atom photofragment imaging studies on the photodissociation dynamics of alkyl radicals 186 , but high-level theoretical studies taking Rydberg/valence interaction into account are needed for further insight.…”
Section: Alkyl Radicals: Tert-butylmentioning
confidence: 99%
“…Alkyl radical photochemistry is of fundamental interest, [7][8][9] and the electronic absorption spectra of alkyl radicals have previously been characterized. 10 The lowest lying electronic excited states available to alkyl radicals are the 3s and 3p z (henceforth referred to as 3p) Rydberg states.…”
Section: Introductionmentioning
confidence: 99%
“…Photodissociation of n-propyl, i-propyl, n-butyl, s-butyl, t-butyl, and 1-pentyl radicals have all produced data that are consistent with the same H-loss mechanisms outlined above for the ethyl radical. 8,[19][20][21] For all of these radicals as for ethyl, the fast and slow H-loss channels occur in a 0.2-0.7:1 ratio, assuming H atoms with different speeds are detected with equal efficiency. Similar experiments on cyclohexyl radical were carried out by Zhang and co-workers but have not been published.…”
Section: Introductionmentioning
confidence: 99%